Investigation on 3-dimensional crack problems in offshore pipeline - See, Wen Bin (Nanyang Technological University, 2024)
This study employed the Finite Element Method (FEM) to analyse the stress distribution in an offshore pipeline containing an embedded crack subjected to internal pressure and axial loading. The pipeline was modelled using Ansys Workbench software, considering corrosion resistance alloy and exterior cracks extrusion. The analysis revealed stress concentrations around the crack tip, with maximum values exceeding the yield strength of the material. Stress intensity factors (SIFs) were calculated, indicating potential crack growth under long-term loading. The findings suggest that the crack can significantly compromise the pipeline's integrity, necessitating further evaluation and possible repair measures. Limitations include the idealized crack geometry and neglecting environmental factors. Future work could investigate different crack configurations and incorporate fatigue loading scenarios.